Konflik Sosial Dalam Novel Tan Karya Hendri Teja Melalui Teori Konflik Lewis A. Coser - Dede Nova Andriyana; Zaky Mubarok (PIKTORIAL : Journal of Humanities, 2020)
This study aims to describe the social conflicts that occur in the novel Tan by Hendri Teja. This research is descriptive research. The object of this research is about social conflicts that occur in novels based on social conflicts according to Lewis A. Coser. These conflicts include realistic conflicts, non-realistic conflicts and positive functions of social conflicts. The data in this study were obtained by analyzing Tan's novel by Hendri Teja using reading and note-taking techniques. the results of this study indicate that there are social conflicts in Tan's novel by Hendri Teja. Realistic conflicts in Tan's novel are arguments, quarrels and differences in views and differences in interests. Non-realistic conflict in the novel is a conflict that aims to relieve tension, at least from one party. And the positive function of social conflict is a way that is taken to maintain, unite, and even to reinforce existing social systems, both individuals and groups or groups. Keyword: Social Conflict, Conflict functionalism, Literary Sociology.